Dual redox groups enable organic cathode material with a high capacity for aqueous zinc-organic batteries. (1st February 2022) - An, Yongkang; Liu, Yu; Tan, Shuangshuang; Xiong, Fangyu; Liao, Xiaobin; An, Qinyou
Highlights: An organic cathode with dual redox groups (TBQPH) for aqueous Zn-organic batteries. Utilize dual redox groups to achieve an ultra-high specific capacity of 455 mAh g −1 . Direct evidence of H + insertion was found by liquid 1 H NMR spectrum. Achieved long cycle capabilities of 10, 000 cycles at 5 and 10 a g −1, respectively. Abstract: Organic cathode materials have recently attracted extensive attention in aqueous zinc-organic batteries (ZOBs) due to their safety, abundant resources, and designability. However, the most as-reported organic materials with a single redox site exhibit limited specific capacities. Herein, benzo [i] benzo [6, 7] quinoxalino [2, 3-a] benzo [6, 7] quinoxalino [2, 3-c] phenazine-5, 8, 13, 16, 21, 24-hexaone (TBQPH) with both carbonyls and pyrazines as redox groups is designed and synthesized as ZOBs cathode material. The dual redox sites in TBQPH enable a high specific capacity of 455.8 mAh g −1 at 0.3 A g −1 owing to the 12-electron reaction mechanism. Ex-situ spectroscopic techniques (especially liquid NMR spectrum) and density functional theory calculations provide strong evidence for the insertion/extraction of hydrogen ions. More importantly, the TBQPH electrode exhibits an ultra-long cycle life of 10, 000 cycles at 10 A g −1 with an average decay of only 0.0022% per cycle, which is attributed to the fast reaction kinetics and low charge transfer resistance. This work inspires new inspiration for designing next-generation high-performance organic electrode materials. Graphical abstract: Image, graphical abstract .